The Effect of Ethanolic Extract of Roselle (Hibiscuss sabdariffa L) on Increasing SOD Activity - Abdul Rahman W; Nurkhasanah Nurkhasanah; Nanik Sulistyani (International Journal of Public Health Science (IJPHS), 2016)
Free radicals were reactive species caused oxidation of lipids membrane and DNA. Superoxide dismutase (SOD) is one of the primary antioxidants to inhibit free radicals. The purpose of this study was to determine the effect of ethanol extract of roselle calyx on SOD enzyme activity of the Sprague Dawley (SD) rats induced by 7.12-dimethylbenzen[a]anthracene (DMBA). The animals age of four weeks divided in to five groups, groups I were normal group. Group II is the negative control group only induced by DMBA 75 mg/kgBW; and group III ,IV , and V were treatment groups that treated by ethanolic extract of roselle calyx at dose of 10, 50 and 100 mg/kgBW/day for 7 days. After treatment with roselle, animals were induced by DMBA 75 mg/kgBW. On day 8 after DMBA induction, animals were fasted for 16 hours and blood was collected to measured SOD activity. Data were analyzed using One Way Analysis Of Variance (ANOVA) and LSD (P <0.05). The result showed the significancies on increasing of SOD activity at 10 mg/kgBW (50.87±1.98), 50 mg/kgBW (69.98±3.58) and 100 mg/kgBW (73.01±6.95) compared with DMBA (43.74±1.95) (p<0,05).